Optimizing radionuclide sequestration in anion nanotraps with record pertechnetate sorption - Qi Sun (Nature Portfolio, 2019)
The elimination of specific contaminants from high concentrations of competitors poses a significant challenge. Here the authors find that modifying the local environment of the direct contact site alters the interaction of a pyridinium-based anion nanotrap with pertechnetate.